A COLLABORATIVE SYSTEM TO MANAGE INFORMATION SOURCES IMPROVING TRANSPORT INFRASTRUCTURE DATA KNOWLEDGE - Cafiso, Salvatore; di Graziano, Alessandro; Pappalardo, Giuseppina (Journal of Engineering and Technological Sciences, 2019)
The present paper describes the WIKI RoadSMap project implemented within a start-up research program. The main objective of the project is to create a system that applies innovative technologies to information gathered to enable the acquisition of greater local knowledge and analysis of issues related to road infrastructure and directly and indirectly connected elements. By applying semantic analysis technology for the extraction, collection, integration and publication of data, WIKI RoadSMap allows users to acquire greater knowledge in order to optimize choices related to road infrastructure. The system allows more detailed and targeted dissemination of data related to the design, management and maintenance of an infrastructure. The source and type of data needed are different and heterogeneous, including information ?posted? by people with private and/or commercial purposes, or available at road agencies and/or public administrations or related to specific surveys carried out. The system platform should be available on the Web and on smartphones, both providing different levels of access and subscriptions. The spread and use of WIKI RoadSMap could have a positive impact on the market with regard to the supply of materials and specialized technical skills and companies operating in the areas of interest.